Ligustrum robustum Intake, Weight Loss, and Gut Microbiota: An Intervention Trial - Zhou, Tao (Evid Based Complement Alternat Med, 2019)
Ligustrum robustum (LR) shows antiobesity effects in animal studies. However, little is known about the effect on human. The present study aimed to investigate the effect of LR intake on weight change in obese women and the role of gut microbiota. Thirty overweight and obese female participants (BMI ≥24 kg/m(2)) were recruited in the current study. The participants drank LR 10g/d for 12 wks. Their body composition and related biomarkers were assessed. Alterations of the gut microbiota were analyzed using 16S rRNA sequencing. The primary outcome was the change in body weight. LR intake resulted in 2.5% weight loss over 12 wks (P<0.01). Change in body fat at 12 wk was -1.77 ± 1.19 kg (P<0.01). In addition, decreased Firmicutes-to-Bacteroidetes ratio (P=0.03), increased richness (the ACE estimator, P<0.01; the Chao1 estimator, P<0.01), and altered representative taxa of the gut microbiota were observed. Bacteroidaceae, Bacteroides, Bacilli, and Lactobacillales were higher while Ruminococcaceae, Enterobacteriaceae, Enterobacteriales, Lachnospiraceae, Clostridia, and Clostridiales were lower at 12 wk. Moreover, LR intervention decreased fasting glucose (P<0.01), serum leptin (P<0.01), and IL8 (P=0.02) and increased HOMA-β (P<0.01). LR intervention moderately decreased the body weight in overweight and obese women and such effect might be due to modulation of gut microbiota.